Quasi‐biennial oscillations in the geomagnetic field: Their global characteristics and origin. Issue 5 (8th May 2017) - Ou, Jiaming; Du, Aimin; Finlay, Christopher C.
Abstract: Quasi‐biennial oscillations (QBOs), with periods in the range 1–3 years, have been persistently observed in the geomagnetic field. They provide unique information on the mechanisms by which magnetospheric and ionospheric current systems are modulated on interannual timescales and are also of crucial importance in studies of rapid core field variations. In this paper, we document the global characteristics of the geomagnetic QBO, using ground‐based data collected by geomagnetic observatories between 1985 and 2010, and reexamine the origin of the signals. Fast Fourier transform analysis of second‐order derivatives of the geomagnetic X, Y, and Z components reveals salient QBO signals at periods of 1.3, 1.7, 2.2, 2.9, and 5.0 years, with the most prominent peak at 2.2 years. The signature of geomagnetic QBO is generally stronger in the X and Z components and with larger amplitudes on geomagnetically disturbed days. The amplitude of the QBO in the X component decreases from the equator to the poles, then shows a local maximum at subauroral and auroral zones. The QBO in the Z component enhances from low latitudes toward the polar regions. At high latitudes (poleward of 50°) the geomagnetic QBO exhibits stronger amplitudes during LT 00:00–06:00, depending strongly on the geomagnetic activity level, while at low latitudes the main effect is in the afternoon sector. These results indicate that the QBOs at low‐to‐middle latitudes and at high latitudes are influenced by different magnetospheric and ionospheric current systems. The characteristics of the multiple peaks in the QBO range are found to display similar latitudinal and local time distributions, suggesting that these oscillations are derived from a common source. The features, including the strong amplitudes seen on disturbed days and during postmidnight sectors, and the results from spherical harmonic analysis, verify that the majority of geomagnetic QBO is of external origin. We furthermore find a very high correlation between the geomagnetic QBO and the QBOs in solar wind speed and solar wind dynamic pressure. This suggests the geomagnetic QBO primarily originates from the current systems due to the solar wind‐magnetosphere‐ionosphere coupling process. Key Points: The geomagnetic QBO at high latitudes is stronger during LT 00:00‐06:00, depending strongly on the geomagnetic activity level The multipeaks of QBO show similar characteristics in latitudinal and local time distributions, suggesting they are from a common source The geomagnetic QBO is found correlated to solar wind parameters and due to the solar wind‐magnetosphere‐ionosphere coupling process